Greenhouse Gas Emissions from Livestock Manure Management in Southwestern Siberia, Russia - Störrle, Maria; Brauckmann, Hans-Jörg; Broll, Gabriele (Sustainable Agriculture Research, 2018)
This study investigates the amounts of greenhouse gas (GHG) emissions due to manure handling within different livestock production systems in Tyumen oblast of Western Siberia. Tyumen oblast occupies approx. 160 000 km² of Asian taiga and forest steppe. The amount of GHGs from manure was calculated as a function of the handling according to current IPCC guidelines for ecozones and livestock production systems. The entire Tyumen oblast has annual 7 400 t methane emissions and 440 t nitrous oxide emissions from manure. Three livestock production systems are prevalent in Tyumen oblast: Mega farms, small farms and peasant farms. The share of mega farms is 81 % (171 kt CO2 eq). Additionally, the slurry system in mega farms causes environmental pollution. GHG emissions and environmental pollution could be reduced by implementing solid manure systems or pasturing, by installing storage facilities for slurry outside the stables and through application of the manure as fertiliser at mega farms. In small farms solid manure systems and a small stocking density of livestock lead to smallest GHG emissions (1 %, 3 kt CO2 eq) from manure. In peasant farming 18 % (38 kt CO2 eq) of GHGs are emitted due to pasturing.